Timing of recurrences of TEM resected rectal neoplasms is variable as per the surveillance practices of one tertiary care institution - Allison C. Keeping (Nature Portfolio, 2021)
Abstract Transanal endoscopic microsurgery (TEM) is widely used for the excision of rectal adenomas and early rectal adenocarcinoma. Few recommendations currently exist for surveillance of lesions excised by TEM. The purpose of this study was to review the surveillance practices and the patterns of recurrence among TEM resected lesions at a tertiary care hospital. A retrospective chart review was performed on all patients who underwent TEM for rectal adenoma or adenocarcinoma before June 2017. In our study population of 114 patients, the final pathology included 78 (68%) adenomas and 36 (32%) adenocarcinomas. Of the adenocarcinomas 23, 9, and 4 were T1, T2, T3 lesions, respectively. Of those, 25 patients opted for surveillance instead of further treatment. The most commonly recommended endoscopic surveillance strategy by our group for both adenomas and adenocarcinomas excised by TEM was flexible sigmoidoscopy every 6 months for 2 years. Recurrences occurred in 4/78 (5.1%) adenoma patients, all found within 16.9 months of surgery, and in 4/25 (16%) adenocarcinoma patients, found between 7.4 and 38.5 months post-surgery. Our data highlights the fact that the timing of recurrences post TEM surgery is variable. Further studies looking at recurrence patterns are needed in order to create comprehensive guidelines for surveillance of these patients.